Investigation of a combination therapy approach for the treatment of melioidosis - Barnes, Kay B.; Richards, Mark I.; Burgess, Gary; Armstrong, Stuart J.; Bentley, Christine; Maishman, Thomas C.; Laws, Thomas R.; Nelson, Michelle; Harding, Sarah V. (Frontiers in Microbiology, 2022)
The efficacy of finafloxacin as a component of a layered defence treatment regimen was determined in vitro and in vivo against an infection with Burkholderia pseudomallei. Doxycycline was down selected from a panel of antibiotics evaluated in vitro and used in combination with finafloxacin in a Balb/c mouse model of inhalational melioidosis. When treatment was initiated at 24 hours post-challenge with B. pseudomallei, there were no differences in the level of protection offered by finafloxacin or doxycycline (as monotherapies) when compared to the combination. There was evidence for improved bacterial control in the groups treated with finafloxacin (as monotherapies or in combination with doxycycline) when compared to mice treated with doxycycline. Survival comparisons of finafloxacin and doxycycline (as monotherapies) or in combination initiated at 36 hours post-challenge, indicated that finafloxacin was superior to doxycycline. Doxycycline was also unable to control the levels of bacteria within tissues to the extent that doxycycline and finafloxacin used in combination or finafloxacin (as a sole therapy) could. In summary, finafloxacin is a promising therapy for use in the event of exposure to B. pseudomallei.